Pemahaman Guru terhadap Gaya Belajar Peserta Didik di Kelas 5 SD Negeri Karanganyar Gunung 02 Semarang - Kusuma, Indra Pradana; Wuryandini, Endang; Miyono, Noor; Khasanah, Siti Khuluqul (ALSYS, 2023)
This research is motivated by the importance of the teacher’s role in understanding the needs of their students, such as the characteristics of students, and the learning styles of students. The purpose of this study was to describe the teacher’s understanding of student’ learning styles, the services provided by the teacher, the constraints experienced by the teacher, and the teacher’s efforts to overcome obstacles to various student learning styles at SDN Karanganyar Gunung 02. This study used a qualitative approach with a descriptive type. The result of the study showed that the 5th grade teachers at SDN Karanganyar Gunung 02 already understood learning styles and understood student’s learning styles. In facilitating student learning styles that have been carried out well, but not all students can be reached by the teacher in the learning process, so that there are students who still feel they do not understand the material presented. In overcoming this, teachers must be able to increase their understanding of the differences in learning styles of each student, and also need to use more varied learning methods so that the learning carried out can reach all the need of students.